Scooby-Doo! World of Mystery 14 Thailand - Emerald Temple - Craft Plus Publishing Ltd (De Agostini Uk Ltd, 2004)
The gang head for the emerald temple in Thailand but bump into some trouble along the way.
Keywords: Juvenile literature-Fiction